Answer:
Step-by-step explanation:
We have been given a recurrence relation and the first term of the sequence .
We can rewrite the given recurrence relation as:
We know that if difference between two consecutive terms is always constant, the sequence is called an arithmetic sequence. So we are dealing with an arithmetic sequence with first term as 4 and common difference as 12.
We can therefore, write an explicit formula for nth terms of the sequence as.
This is the required explicit function rule for the given sequence.
-5+x/3=-11
Answer:
The interest Cody gets in 2 years be $56 .
Step-by-step explanation:
Formula
As given
Cody has $700 in a savings account that pays 4% interest .
Principle = $700
Interest = 4%
Time = 2 years
Put in the formula
Simple interest = $ 56
Therefore the interest Cody gets in 2 years be $56 .
Answer:
Step-by-step explanation:
x^2 + 12x = -11
x^2 + 12x + 11 = 0
(x + 1)(x + 11) = 0
x + 1 = 0 x + 11 = 0
x = -1 x = -11
x = -1, x = -11